A Guide to Sources of Texas Criminal Justice Statistics - Harnsberger, R. Scott (University of North Texas Press, 2011)
This reference work is a resource for those needing assistance in locating Texas criminal justice statistics. R. Scott Harnsberger has compiled more than 600 entries describing statistical sources for Texas crime; criminals; law enforcement; courts and sentencing; adult and juvenile corrections; capital punishment and death row; victims of crime; driving/boating under the influence; traffic fatalities; substance abuse and treatment; polls and rankings; and fiscal topics such as appropriations, revenues, expenditures, and federal aid. The sources for these statistics originate primarily, but not exclusively, from federal and State of Texas agencies, boards, bureaus, commissions, and departments. The following types of publications are included: annual, biennial, and biannual reports; reports issued in series; analytic and research reports; statistical compilations; budgets and other fiscal documents; audits, inspections, and investigations; census publications; polls; projections; rankings; surveys; continuously updated online resources; and datasets. Harnsberger has annotated the entries to provide sufficient detail to enable users to decide whether the listed resources merit further investigation. Additional notes contain URLs and information regarding the scope of the published data; title changes; related publications; and the availability of earlier data, previous editions, online tables, and datasets. This book will prove to be a valuable resource for students, faculty, researchers, government officials, and individuals in the law enforcement, correctional, and judicial professions.